A new genus of Philorheithridae (Trichoptera) from Madagascar - Weaver Iii, John S.; Gibon, François-Marie; Chvojka, Pavel (Zootaxa, 2008)
Afrorheithrus genus novum and three species (Afrorheithrus fallax sp. nova, A. mirus sp. nova, A. admirabilis sp. nova) of the family Philorheithridae (Trichoptera) are described from Madagascar, representing the first described philorheithrids from the Afrotropical Region.